Pelatihan Inseminasi Buatan pada Mahasiswa Magang Merdeka Belajar Kampus Merdeka (MBKM) - Nugraha, Angga; Jabir, Usman; Novly, Novly; Shapri, Shapri; Sukri, Muhamamad Yusran (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Artificial Insemination Training is an activity carried out to teach students about the techniques needed in collecting, processing, and storing cow semen properly and correctly. The purpose of this training is so that students can know the handling of bovine semen that is done properly and correctly to maintain the quality and viability of semen besides that students can also choose superior males, semen collection techniques, semen quality testing, handling, and treatment of semen and the right strange method which is expected after mastering students can apply it directly to the community. This training was conducted at the Artificial Insemination and Semen Production Service Unit in Pucak Village, Tompobulu Subdistrict, Maros District, Livestock and Animal Health Service Office of South Sulawesi Province. The object of this training was beef cattle in the Artificial Insemination Service Unit. The insemination stage is carried out through 6 stages, namely the semen storage stage (drum storage), semen quality evaluation stage (laboratory), equilibration process stage, pre-freezing stage, freezing stage, and straw storage stage. The method used in this activity is the lecture method and hands-on practice guided by field supervisors. The results of this PKM artificial insemination training are that students learn various aspects related to artificial insemination training